Landscape Diversity Influences Dispersal and Establishment of Pest with Complex Nutritional Ecology - Ferreira, Claudia P. [UNESP]; Esteva, Lourdes; Godoy, Wesley A. C.; Consoli, Fernando L. (Springer, 2014)
We studied the effects of landscape structure on species with resource nutritional partition between the immature and adult stages by investigating how food quality and spatial structure of a landscape may affect the invasion and colonization of the insect pest, Diabrotica speciosa. To this end, we formulated two bidimensional stochastic cellular automata, one for the insect immature stage and the other for the adult stage. The automata are coupled by adult oviposition and emergence. Further, each automata site has a specific culture type, which can affect differently the fitness attributes of immatures and adults, such as mortality, development and oviposition rates. We derived the mean-field approximation for these automata model, from which we obtained conditions for insect invasion. We ran numerical simulations using entomological parameters obtained from laboratory experiments (using bean, soybean, potato, and corn crops), and we compared the results of the automata with the ones given by the mean-field approximation. Finally, using artificially generated landscapes, we discussed how the structured heterogeneous landscape can affect dispersal and establishment of insect populations.
Keywords: Basic reproduction number; Cellular automata; Diabrotica speciosa; Fragmented landscape; Mean-field approximation